Measurement Invariance and Intergenerational Parallelism of General Self-Efficacy in Adolescent and Parent Dyads - Lei, Hui; Yuan, Yanyun; Wang, Zhihang; Chen, Jianshi; Li, Zhihua (Frontiers in Psychology, 2020)
General self-efficacy refers to global beliefs about one’s capabilities across a variety of tasks or conditions. It is regarded as an important, relatively stable, motivational trait, and is associated with positive outcomes in a wide range of domains. The general self-efficacy scale (GSE) is the most commonly used measure to evaluate general self-efficacy among adults and youths. This study aimed to examine the measurement invariance of the GSE across age groups among adolescent and parent dyads, and to investigate the intergenerational parallelism of general self-efficacy and the moderating roles of parents’ gender and family socioeconomic status (SES). Participants were 807 adolescent/parent dyads. Multi-group confirmatory factor analysis revealed that full metric and scalar measurement invariance held. Regression analysis showed that parents’ self-efficacy significantly predicted their children’s self-efficacy (β = 0.232, p < .001). Multiple regression analysis indicated family SES played a moderating role (β = 0.066, p < .001), although parents’ gender did not (β = -0.053, p = .288). The results demonstrated the GSE’s measurement invariance across age, and further supported use of the GSE among adults and adolescents. Moreover, our findings provided evidence for the presence of this kind of intergenerational parallelism and the moderating role of family SES.